Tinjauan Yuridis Terhadap Eksistensi Tradisi Maccera Tappareng Dikaitkan Dengan Ekosistem Kawasan Danau Tempe - Makmur, Andi Dadi Mashuri; SInta; Sulaeman; Yustiana (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2026)
This study aims to analyze the legal status of the Maccera Tappareng tradition within the national environmental law framework and its contribution to the preservation of the Lake Tempe ecosystem. Using normative legal research methods with a socio-legal approach, this study explores the convergence between customary norms and formal regulations such as Law No. 32 of 2009 concerning Environmental Protection and Management. The results of the study indicate that Maccera Tappareng is not merely a symbolic ritual, but rather an effective customary law instrument (living law) in regulating the sustainable use of aquatic resources. Integrating these values ​​into regional policies is crucial to addressing ecosystem degradation due to anthropogenic pressures such as the use of inappropriate electric nets and nets, which pose a serious threat to environmental and traditional sustainability. The research method used is empirical law with a sociological approach, through data collection in the form of interviews and field observations. Factors influencing the existence of this tradition include community awareness and behavior, environmental damage due to illegal activities, the role of government in supervision and outreach, and the close relationship between tradition and the lake ecosystem. This study emphasizes the importance of collaboration between the government, customary leaders, and the community in maintaining environmental and cultural sustainability